2017
DOI: 10.1148/radiol.2017161604
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced US-assisted Percutaneous Nephrostomy: A Technique to Increase Success Rate for Patients with Nondilated Renal Collecting System

Abstract: Purpose To perform a single-center study of contrast material-enhanced ultrasonography (US)-assisted percutaneous nephrostomy (PCN) for patients with nondilated renal collecting system. Materials and Methods An international review board approved this retrospective study with waiver of informed consent for participation, and the study was approved by the Ethical Committee. From November 2011 to September 2015, 47 patients (mean age, 51.9 years ± 16.2 [standard deviation]; range, 18-80 years) with clinical nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
(55 reference statements)
0
11
0
1
Order By: Relevance
“…A total of 12 studies (all case series) fall into this miscellaneous section, which includes 4 categories of CEUS assisted procedures: (1) US‐guided abscess drainage; (2) US‐guided percutaneous nephrostomy; (3) US‐guided biliary interventions; and (4) hepatic and splenic hemorrhage. In the first 3 categories, a diluted contrast solution (ie, 0.1 mL of SonoVue in 20 mL of saline) is injected directly in the catheter or needle to visualize the exact location of the cavity or tissue around the catheter or needle tip: so‐called intracavitary CEUS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 12 studies (all case series) fall into this miscellaneous section, which includes 4 categories of CEUS assisted procedures: (1) US‐guided abscess drainage; (2) US‐guided percutaneous nephrostomy; (3) US‐guided biliary interventions; and (4) hepatic and splenic hemorrhage. In the first 3 categories, a diluted contrast solution (ie, 0.1 mL of SonoVue in 20 mL of saline) is injected directly in the catheter or needle to visualize the exact location of the cavity or tissue around the catheter or needle tip: so‐called intracavitary CEUS.…”
Section: Resultsmentioning
confidence: 99%
“…In 2 series of 45 and 47 CEUS‐guided percutaneous nephrostomies, respectively, successful catheter placement was reported in 100% . Very remarkable and with great clinical potential, the latter study included only patients with nondilated pelvises, whereas the former study reported that CEUS could show the site of obstruction (renal pelvis, ureter, or urinary bladder) in all cases.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasound contrast agents can be inserted into a nephrostomy tube/access catheter to verify the location of the tip. So far, CEUS‐guided nephrostomy has been used mainly in difficult cases, especially when the urinary system is not dilated . A CEUS nephrostogram can also be useful in cases in which radiation and contrast minimization are paramount, such as children, pregnant women, and patients with chronic kidney disease .…”
Section: Genitourinary Interventionsmentioning
confidence: 99%
“…The ability to add to the baseline ultrasound examination and to perform a CEUS examination safely would be advantageous. The intravenous application of UCA allows the safe and rapid cannulation of the dilated pelvicalyceal system [8] and insertion of a nephrostomy drainage catheter, even if the system is not prominently dilated [9]. This can be followed by a UCA catheter injection (intra-cavitary CEUS) to demonstrate the correct positioning of the drainage tube, without the need for fluoroscopy [10,11].…”
mentioning
confidence: 99%
“…Die Möglichkeit, CEUS ergänzend zur Basisultraschalluntersuchung sicher durchzuführen, wäre von Vorteil. Die intravenöse UCA-Gabe ermöglicht die sichere und schnelle Kanülierung des erweiterten Nierenbeckenkelchsystems [8] und die Anlegung eines Nephrostomie-Drainagekatheters, auch wenn das System nicht markant dilatiert ist [9]. Anschließend kann eine UCA-Katheter-Injektion (intrakavitäre CEUS) durchgeführt werden, um die korrekte Positionierung des Drainageschlauchs ohne Einsatz der Fluoroskopie darzustellen [10,11].…”
unclassified